Association between the brief inventory of neurocognitive impairment (BINI) and objective cognitive testing among persons with opioid use disorders in drug treatment. Issue 2 (15th October 2020) - Copenhaver, Michael M.; Sanborn, Victoria; Shrestha, Roman; Mistler, Colleen; Gunstad, John
Abstract: The current study examined the association between subjective cognitive dysfunction and objective test performance in persons enrolled in drug treatment and stabilized on methadone maintenance therapy (MMT). A total of 177 participants completed the self-reported brief inventory of neurocognitive impairment (BINI) and NIH Toolbox test battery. In participants with neurocognitive dysfunction, scores on all BINI subscales were negatively associated with objective performance on the NIH Toolbox (BINI Global r = −0.26, p  = 0.01; BINI Subscales ranging −0.22 to −0.32, all p 's < 0.03). Using cutoff scores, results showed participants who scored above the cutoff on the BINI Learning subscale demonstrated significant evidence of objective neurocognitive dysfunction on the NIH Toolbox (65% vs. 35%; χ 2 = 6.57, p  = 0.02), suggesting possible clinical utility. Future studies are needed to determine the feasibility of using the BINI to inform the accommodation of patients with specific neurocognitive profiles to optimize treatment outcomes.